Campus sustainability in the European Union andTurkey: developing a holistic approach in Turkey - Ongan, Gonca (My University, 2014)
Yeni bilgi oluşturmada ve yaratıcılığı teşvik etmede toplumda önemli bir yere sahip olan Yüksek Öğretim Kurumları küresel sürdürülebilirliğin ihtiyaçlarından sorumlu tutulmalıdırlar. 1980’lerin başından beri dünyada çevresel duyarlılığın artması ile gelişmeye başlayan sürdürülebilir kampüs konsepti Avrupa Birliği (AB) Üye Ülkeleri’nde de hem yasal çerçevede hem de gönüllü uygulamalar ile hayata çoktan geçmiştir. Türk Yüksek Öğretim Kurumları bu gelişmelere karşılık verememiştir. Bu tez sürdürülebilir kampüs konseptini tanıtırken, bu konseptin önemli bir parçası olan kampüslerde enerji tüketiminden yola çıkmış ve AB ve Türkiye’de enerji, enerji verimliliği ve binalarda enerji verimliliğini incelemiştir. Yüksek Öğretim Kurumlarının ulusal bir sorun olan enerji konusuna yaklaşımları sürdürülebilir kampüs uygulamaları çerçevesinde incelendiğinde AB’deki üniversitelerin Türkiye’deki üniversitelere göre oldukça ileride oldukları tespit edilmiştir. Ayrıca, tez sürdürülebilir kampüs uygulamalarının başarılı olması için Yüksek Öğretim Kurumlarının sürdürülebilirliği çevresel, sosyal ve ekonomik boyutu ile bütünsel bir yaklaşım ile ele almaları gerektiğini, sürdürülebilir kampüs starteji ve yol haritasının önemini savunmaktadır. Bu bağlamda, Koç Üniversitesi (KU) Rumelifeneri Kampüsü’nün vaka analizi yapılarak, KU için sürdürülebilir kampüs stratejik plan ve yol haritası geliştirilmiş Türkiye’nin AB uyum sürecini desteklemek için Yüksek Öğretim Kurumlarının sürdürülebilir kampüs uygulamalarını nasıl kullanabilecekleri gösterilmiştir. Bu çalışma sonucunda KU’nun çevresel, sosyal ve ekonomik sürdürülebilirlik kapsamında var olan taahhütlerini kolaylıkla ileri götürerek Türkiye’de bütünsel yaklaşımı uygulayan bir sürdürülebilir kampüs olabileceği tespit edilmiştir

Higher Education Institutions (HEIs) should be responsible for the needs of global sustainability because HEIs play an essential role in society, creating new knowledge and fostering innovation. The sustainable campus concept has been rising among HEIs in the world since the 1980s, and different implementations have started in many Member States of the European Union (EU) both at legal and voluntary levels. However, HEIs in Turkey have been lagging behind. In this regard, this thesis highlights the importance of campus sustainability by examining HEIs in the EU and Turkey in the context of energy outlook, approaches to energy efficiency and energy efficiency in buildings. Energy consumption on university campuses, particularly, is considered one of the most important components of campus sustainability. A comparison of EU HEIs and a case study in Turkey demonstrate how HEIs could play a role in responding to national challenges in energy issues in the context of campus sustainability, as European HEIs are far beyond the Turkish HEIs. In addition, even though energy consumption is important in campus sustainability, a university should take a holistic approach to environmental, social and economic aspects of sustainability and develop a campus sustainability strategy and road map to be successful. In this regard, the KU Rumelifeneri Campus is chosen as a campus sustainability case study to develop a holistic approach in Turkey demonstrating how Turkish HEIs could support Turkey’s harmonization process to the EU through successful sustainable campus implementations. The KU sustainable campus strategic plan and road map were developed and suggestions were made based on campus sustainability criteria. Results indicate that campus sustainability at KU should be beyond green as the university has already made strong commitments on environmental, social and economic aspects of sustainability.
Keywords: Avrupa Birliği; Öğrenim ve Öğretim_Kampüs; Yüksek Öğrenim_Üniversite_Koç Üniversitesi